Social isolation and air quality impacts: the Rio de Janeiro case study (Research, Society and Development, 2020)
Many debates about environmental issues surfaced with the advent of the new coronavirus and social distancing. Therefore, the present article aimed to investigate air quality impacts in Rio de Janeiro, during social isolation period. In order to confirm air pollutants, decrease, for example NO and particulate material, documents such as legislations, technical standards, scientific articles published in this period, were analyzed during the studied period. Furthermore, the article sought to bring awareness about the short temporality of the air quality improvement, since without more sustainable forms of production, in a little while, those pollutants may increase again.